Don't make me laugh - Stevenson, James, 1929- (New York : Farrar, Straus and Giroux, 1999)
Readers are requested not to laugh or do anything to influence the behavior of various animal characters in this book.
"Frances Foster books."
1 5 8 9 12 13 18 19 29 31 34 36 38 39
Keywords: Laughter -- Fiction; Behavior -- Fiction; Animals -- Fiction